Global Moral Hazard, Capital Account Liberalization and the 'Overlending Syndrome' - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper, 1999)
The removal of government guarantees in borrowing countries does not eliminate the moral hazard problem posed by the existence of deposit guarantees in lender countries. The paper shows that, after restrictions on international capital flows are lifted, banks in low-risk developed countries benefit from lending funds captured in home markets at low deposit rates to high-risk/high-yield projects in emerging economies, even though these projects command lower expected returns. This, in turn, has a negative impact on bank profitability in the borrowing country, even when foreign funds are intermediated through domestic banks. The results are consistent with the surge in international bank lending flows that led to recent banking crises in Asia.